Microcrystalline Zinc Coordination Polymers as Single‐site Heterogeneous Catalysts for the Selective Synthesis of Mono‐oxazolines from Amino Alcohol and Dinitriles. Issue 12 (24th May 2016) - Wang, Junning; Huang, Chao; Gao, Kuan; Wang, Xiaolu; Liu, Mengjia; Ma, Haoran; Wu, Jie; Hou, Hongwei
Abstract: In our effort to develop coordination polymers (CPs)‐based single‐site catalysts for the selective synthesis of mono‐oxazolines, two Zn‐based CPs, [Zn6 (idbt)4 (phen)4 ⋅3 H2 O] n (1 ) and [Zn3 (idbt)2 (H2 O)4 ⋅2 H2 O] n (2 ) (H3 idbt= 5, 5′‐(1 H ‐imidazole‐4, 5‐diyl)‐bis‐(2 H ‐tetrazole), phen=1, 10‐phenanthroline) have been synthesized. They exhibit two‐dimensional structure and contain isolated and accessible catalytically active sites, mimicking the site isolation of many catalytic enzymes. Micro CPs1 and2 are obtained by using surfactant‐mediated hydrothermal methods, and an investigation is conducted to explore how different surfactants affect their morphologies and particle sizes. Furthermore, micro1 and2 have shown to be effective heterogeneous catalysts for the reaction of amino alcohols and aromatic dinitriles, and exerted a significant influence on the selectivity of the catalytic reactions, yielding mono‐oxazolines as the major reaction product. Abstract : To improve the catalytic efficiency, microscale coordination polymers (CPs)1 and2 (see scheme) have been obtained by using surfactant‐mediated hydrothermal methods. Furthermore, micro CPs1 and2 have shown to be effective heterogeneous catalysts for the selective synthesis of mono‐oxazolines from amino alcohols and dinitriles, which could be attributed to their immobilizing well‐defined catalytic sites.